Effect of composition in the development of carbamazepine hot-melt extruded solid dispersions by application of mixture experimental design. (18th December 2013) - Djuris, Jelena; Ioannis, Nikolakakis; Ibric, Svetlana; Djuric, Zorica; Kachrimanis, Kyriakos
Abstract: Objectives: This study investigates the application of hot-melt extrusion for the formulation of carbamazepine (CBZ) solid dispersions, using polyethyleneglycol-polyvinyl caprolactam-polyvinyl acetate grafted copolymer (Soluplus, BASF, Germany) and polyoxyethylene–polyoxypropylene block copolymer (Poloxamer 407). In agreement with the current Quality by Design principle, formulations of solid dispersions were prepared according to a D-optimal mixture experimental design, and the influence of formulation composition on the properties of the dispersions (CBZ heat of fusion and release rate) was estimated. Methods: Prepared solid dispersions were characterized using differential scanning calorimetry, attenuated total reflectance infrared spectroscopy and hot stage microscopy, as well as by determination of the dissolution rate of CBZ from the hot-melt extrudates. Key findings: Solid dispersions of CBZ can be successfully prepared using the novel copolymer Soluplus. Inclusion of Poloxamer 407 as a plasticizer facilitated the processing and decreased the hardness of hot-melt extrudates. Regardless of their composition, all hot-melt extrudates displayed an improvement in the release rate compared to the pure CBZ, with formulations having the ratio of CBZ : Poloxamer 407 = 1 : 1 showing the highest increase in CBZ release rate. Conclusions: Interactions between the mixture components (CBZ and polymers), or quadratic effects of the components, play a significant role in overall influence on the CBZ release rate.